Between function and structure: Vladimir Propp’s morphology in the Arabic short story Habbat at-Tut - Wafiroh, Nayla Izzah; Fauzi, Moh. Sony (Al-Lisan: Jurnal Bahasa, 2025)
Background: The short story Ḥabbat al-Tūt by Kamil Kailani narrates a mother’s sacrifice to save her child without expecting anything in return. Its theme remains highly relevant to contemporary society, where social relationships are often shaped by interests rather than sincerity. Aims: The present study seeks to examine how narrative elements contribute to the construction of the plot, the development of characters, and the articulation of the underlying message intended by the author. Methods: This study employed a descriptive qualitative design. The primary data consisted of Kamil Kailani's Arabic short story Ḥabbat al-Tūt, while the secondary sources comprised scholarly books, journal articles, proceedings, and web-based references related to Vladimir Propp's structuralist framework and short story analysis. Data were analysed through a narrative structural approach, which involved systematic procedures of close reading, classification of narrative functions, reconstruction of the story's structure, and interpretation of its thematic and moral dimensions. Results: The study identified 19 relevant functions within the narrative of Ḥabbat al-Tūt, each presenting variations in the way the main character gradually overcomes challenges. One such function is interdiction, which reflects the rules or restrictions that characters are required to follow. In the story, for instance, Kuku is instructed to eat only small seeds, as his body is not yet strong enough. Implications: The short story highlights the sincerity of a mother's love, offering values of love, responsibility, and sacrifice that remain meaningful for readers. By applying Propp's 19 narrative functions, this study demonstrates the relevance of structuralist analysis to modern Arabic literature. It shows how narrative form conveys emotional and moral significance within the Middle Eastern cultural context.